KAJIAN YURIDIS MENGENAI PERLINDUNGAN HUKUM DAN PENERAPANNYA TERHADAP KAUM LESBI GAY BISEKSUAL DAN TRANSGENDER (LGBT) DI INDONESIA - NIM. A01110101, SHEILA KHAIRUNNISA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstrac The Indonesian state is a state based on law, according to the statement about the Indonesian nation written in the explanation of the 1945 Constitution. All the course of its pattern of government at any time and place, is always resolved by the provisions of the applicable law, as well as the nature of humans who have rights. basic rights as Indonesian citizens and the basic rights they have as human beings living in this world. The legal protection provided by the government creates a sense of security for every citizen. However, what about citizens who choose to like the same sex (lesbian and gay), as well as the desire to be a